The lure of liking and being liked Philippine cuisine at the turn of the nineteenth century - Sta. Maria, Felice (2021)
When the Philippine archipelago was attached to the Spanish Empire from 1565 to 1898, native food and drink were exposed to new foreign ingredients, cooking techniques and technologies, tastes and preparations, as well as terms and status indicators. While there were required foods and food ways prescribed by Roman Catholicism as it acquired converts, there were also culinary attractions that made their way into Philippine culinary heritage seemingly by independent choice. Their Spanish-ness may have been one reason they were liked. There also could have been practical reasons for their acceptance ranging from portability to adaptability, as well as subjective reasons like taste preferences. A trio of locally authored recipe books published in the early twentieth century suggests how European encounters had blended with the Philippines' pre-colonial insular Asian food and eating traditions. These are statements of culinary carryovers from the Spanish colonial era that had become Filipino. Nevertheless, the staying power of food introduced from abroad depends on whether it is liked or not by the host culture.
Keywords: Food--Philippines--History; Cooking, Philippine--History; Cooking, Philippine; Philippine cooking; Malolos Congress